FACTORS AFFECTING GENERATIONAL MILLENNIALS' DESIRE TO SPEND MONEY ON WAQF - abdul latif; Rusyda Afifah Ahmad; Meichio Lesmana; Fikriyyatun Nabila (IAIN Ponorogo, 2022)
AbstractWaqf is currently in the limelight for its contribution to social activities. Waqf offers a great deal of potential, especially given the current urgency to assist in financing education. Laziswaf is one of the initiatives aimed at promoting the sustainability of education. From here, the author observes students who drop out of school due to a lack of funds, whereas the establishment of a cashWaqf institution at a tertiary institution aims to assist students who lack funds in order for them to continue their studies. As a result, the goal of this study is to investigate the effects of religiosity, knowledge, and financial attitudes on students in educational institutions that have Waqf institutions in East Java. In this study, qualitative and quantitative methodologies were employed. This study used SEM with LISREL software version 8.70. The SEM technique is considered the best analytical strategy to examine multiple effects between independent and dependent variables simultaneously. 425 respondents made up the sample for this study. As a result of the study, the factors of knowledge and religion have less of an impact than the factor of financial attitude, which has a greater impact. Thus, this indicates that student waqf interest is less influenced by H1-knowledge and H2-spiritual understanding and, on the other hand, is more influenced by H3-financial attitudes than by H1 and H2. In a way, a student's desire to spend their money on charity can be inferred mostly from their financial outlook. AbstrakWakaf saat ini menjadi pusat perhatian karena kontribusinya dalam kegiatan sosial. Wakaf menawarkan banyak potensi, terutama mengingat urgensinya saat ini untuk membantu pembiayaan pendidikan. LAZISWAF merupakan salah satu inisiatif yang bertujuan untuk mendorong keberlanjutan pendidikan. Dari sinilah penulis melihat kasus siswa yang putus sekolah karena tidak memiliki dana, sedangkan pendirian lembaga wakaf tunai di perguruan tinggi bertujuan untuk membantu kasus siswa yang kekurangan dana agar dapat melanjutkan studinya. Maka penelitian ini mempunyai tujuan untuk mengkaji bagaimana pengaruh religiusitas, pengetahuan, dan sikap keuangan terhadap niat wakaf santri pada lembaga pendidikan yang memiliki lembaga wakaf di Jawa Timur. Dalam penelitian ini, metodologi kualitatif dan kuantitatif digunakan. Penelitian ini menggunakan SEM dengan software LISREL versi 8.70. Teknik SEM dianggap sebagai strategi analitik terbaik untuk menguji beberapa efek antara variabel independen dan dependen secara bersamaan. Penelitian ini menggunakan sampel sebanyak 425 responden. Penelitian ini menunjukkan bahwa sikap finansial lebih mempunyai pengaruh yang besar dibandingkan dengan faktor religiusitas dan pengetahuan. Dengan demikian, hal ini menunjukkan bahwa minat wakaf siswa kurang dipengaruhi oleh H1-pengetahuan dan H2-pemahaman spiritual dan sebaliknya lebih dipengaruhi oleh H3-sikap keuangan dibandingkan H1 dan H2. Di satu sisi, keinginan siswa untuk membelanjakan uang mereka untuk amal sebagian besar dapat disimpulkan dari pandangan keuangan mereka.